If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5b + 6)(5b + -6)(5b + 6) = 0 Reorder the terms: (6 + 5b)(5b + -6)(5b + 6) = 0 Reorder the terms: (6 + 5b)(-6 + 5b)(5b + 6) = 0 Reorder the terms: (6 + 5b)(-6 + 5b)(6 + 5b) = 0 Multiply (6 + 5b) * (-6 + 5b) (6(-6 + 5b) + 5b * (-6 + 5b))(6 + 5b) = 0 ((-6 * 6 + 5b * 6) + 5b * (-6 + 5b))(6 + 5b) = 0 ((-36 + 30b) + 5b * (-6 + 5b))(6 + 5b) = 0 (-36 + 30b + (-6 * 5b + 5b * 5b))(6 + 5b) = 0 (-36 + 30b + (-30b + 25b2))(6 + 5b) = 0 Combine like terms: 30b + -30b = 0 (-36 + 0 + 25b2)(6 + 5b) = 0 (-36 + 25b2)(6 + 5b) = 0 Multiply (-36 + 25b2) * (6 + 5b) (-36(6 + 5b) + 25b2 * (6 + 5b)) = 0 ((6 * -36 + 5b * -36) + 25b2 * (6 + 5b)) = 0 ((-216 + -180b) + 25b2 * (6 + 5b)) = 0 (-216 + -180b + (6 * 25b2 + 5b * 25b2)) = 0 (-216 + -180b + (150b2 + 125b3)) = 0 (-216 + -180b + 150b2 + 125b3) = 0 Solving -216 + -180b + 150b2 + 125b3 = 0 Solving for variable 'b'. The solution to this equation could not be determined.
| W-1.6=.3 | | -1.25q-12.5=8.35 | | -13*-13= | | 14x-9=22 | | -13x-13= | | 74-5x=13x+24 | | 0.75q+2.5=-6.5 | | x+x(.10)=26 | | -18=-4z+12 | | 3y-8=-17 | | 15-4x=2(3x+1) | | -2n^2+6n-108=0 | | -23m-17=15m-1 | | 5x-1=3+3x | | 12-f=22 | | 4a+7(2a-5)-5(3a+1)=50 | | -12+9-6= | | 25x^2-25x=0 | | x(-25+16x)=0 | | -14+6= | | -2(m+7)=-27 | | 17-2a+5a-1= | | 7X+1-5X=15 | | 17=T-9 | | 176-6x=6x+8 | | X+3=21 | | 10x-8=-148 | | 2=3x-8 | | (c-6)(c-13)=0 | | 8x+9-3x= | | 10x^2=-4x | | -4x+10y=0 |